2019
DOI: 10.1080/01419870.2019.1654114
|View full text |Cite
|
Sign up to set email alerts
|

Taste or statistics? A correspondence study of ethnic, racial and religious labour market discrimination in Germany

Abstract: In this study we compare rates of discrimination across German-born applicants from thirty-five ethnic groups in which various racial and religious treatment groups are embedded, this study allows us to better distinguish taste and statistical sources of discrimination, and to assess the relative importance of ethnicity, phenotype and religious affiliation as signals triggering discrimination. The study is based on applications to almost 6,000 job vacancies with male and female applicants in eight occupations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(37 citation statements)
references
References 42 publications
1
34
0
2
Order By: Relevance
“…In addition to ethnic discrimination against people with Arabic names, religious discrimination might come on top, or ethnic and religious belonging might coincide. A handful of studies have revealed that religious discrimination against Muslim minorities when it comes to schools and the labor market (e.g., Adida et al 2010;Di Stasio et al 2019;Drydakis 2010;Koopmans, Veit, and Yemane 2019;Olsen et al 2020;Piern e 2013;Valfort 2018;Weichselbaumer 2016;Wright et al 2013) is undeniable and sometimes comes on top of ethnic discrimination. This also extends to Muslim organizations as lost-letter experiments in Germany (Koopmans and Veit 2014) and Switzerland (Berger and Berger 2019) show.…”
Section: T H E O R E T I C a L B A C K G R O U N Dmentioning
confidence: 99%
“…In addition to ethnic discrimination against people with Arabic names, religious discrimination might come on top, or ethnic and religious belonging might coincide. A handful of studies have revealed that religious discrimination against Muslim minorities when it comes to schools and the labor market (e.g., Adida et al 2010;Di Stasio et al 2019;Drydakis 2010;Koopmans, Veit, and Yemane 2019;Olsen et al 2020;Piern e 2013;Valfort 2018;Weichselbaumer 2016;Wright et al 2013) is undeniable and sometimes comes on top of ethnic discrimination. This also extends to Muslim organizations as lost-letter experiments in Germany (Koopmans and Veit 2014) and Switzerland (Berger and Berger 2019) show.…”
Section: T H E O R E T I C a L B A C K G R O U N Dmentioning
confidence: 99%
“…Similarly, Weichselbaumer (2020) finds that ethnically Turkish women applying for jobs in Germany received much lower callback rates if they wear a headscarf in their photo than if they do not (photos are standard in job applications in Germany). Using a regression procedure, Koopmans, Veit, and Yemane (2019) found some evidence that some of the discrimination against Turkish immigrants and Muslims may reflect evaluations of cultural differences from German people. In the U.S., Kang et al (2016) find that Asian-American and Black applicants who "whitewash" their resumes (either by changing their first name or by removing experience with minority organizations from their CVs) receive significantly more callbacks than applicants who do not, although this finding might also reflect clarity of the race signal or concerns about language proficiency.…”
Section: Cultural Distance Increases Discriminationmentioning
confidence: 99%
“…Similarly, DiStasio et al (2019) analyze GEMM data from five countries and found that immigrants who disclosed participation in Muslim organizations on their CV experienced additional discrimination, although the effect was weaker than the effect of origins from Islamic-majority countries. Koopmans, Veit, and Yemane (2019) included both membership in religious organizations on the CV and race based on appearance in a photo in a correspondence study in Germany. They found that both Muslim organizational participation and Black race were negatively associated with callbacks, but effects were slightly larger for Black race.…”
Section: Muslims and Ethnic Groups From Muslim-majority Countries Are Discrimination Targetsmentioning
confidence: 99%
“…At the same time, the disadvantage they faced is relatively modest, especially if compared with the treatment afforded to non-white ethnic minorities, and concentrated in non-graduate occupations such as cooks, admin and clerk jobs. Second, we broaden the geographical reach of field experiments on hiring discrimination that, with a few exceptions ( Koopmans et al, 2019 ; Thijssen et al, 2019 ), have so far limited their focus to non-Western ethnic minorities or compared the latter to a single European group ( Baert et al, 2017 ; McGinnity and Lunn, 2011 ). Third, our analysis reveals that only EU12 applicants benefitted from the cosmopolitanism of the Greater London Area, where they were treated on a par with the white British group.…”
Section: Introductionmentioning
confidence: 99%